Zarit Burden Interview sebagai Instrumen Utama dalam Pengukuran Beban Caregiver pada Pasien Paliatif - Rima Hanifati; Dewi Gayatri (FORIKES, 2024)
Caregivers are close family members or other people with a professional health background. In the care of advanced cancer patients who are treated palliatively, caregivers have a burden on physical, emotional and financial health. Holistic assessment for caregivers is expected to improve quality of life, understanding of the disease so that it can help in holistic patient care and can make medical decisions. This study aimed to determine the instruments used to measure caregiver burden in palliative patients. This study was a systematic review conducted in accordance with the PRISMA standard. The databases used in the literature search were EBSCOhost, Science Direct, and Scopus. The results of this systematic review focused on 22 articles and contained 14 instruments for measuring caregiver burden, namely Zarit Burden Interview, Caregiver Strain Index, Burden Scale for Family Caregiver, Caregiver Burden Inventory, World Health Organization Quality of Life Instrument, Short Form, Caregiver Reaction Assessment, Caregiving Consequences Inventory, Caregiver Burden Scale, Brief Symptom Inventory, Caregiver’s Burden Scale in End of Life, General Health Questionnaire, Thai Burden Interview, Family Appraisal of Caregiving Questionnaire and Family Caregiver Burden. The conclusion of this systematic review is that the Zarit Burden Interview (ZBI) is the most widely used instrument for measuring caregiver burden in palliative patients.Keywords: caregiver burden; patients; palliative care ABSTRAK Caregiver adalah keluarga terdekat atau orang lain dengan latar belakang profesional kesehatan. Dalam perawatan pasien kanker dengan stadium lanjut dengan perawatan paliatif, caregiver memiliki beban kesehatan fisik, emosional dan finansial. Penilaian secara holistik bagi caregiver diharapkan dapat meningkatkan kualitas hidup, pemahaman tentang penyakit sehingga dapat membantu dalam perawatan pasien secara holistik dan dapat mengambil keputusan medis. Studi ini bertujuan untuk mengetahui instrumen yang digunakan untuk mengukur beban caregiver pada pasien paliatif. Studi ini merupakan tinjauan sistematis yang dilakukan sesuai dengan standar PRISMA. Database yang digunakan pada pencarian literatur adalah EBSCOhost, Science Direct, dan Scopus. Hasil tinjauan sistematis ini berfokus pada 22 artikel dan di dalamnya terdapat 14 instrumen untuk pengukuran beban caregiver yaitu Zarit Burden Interview, Caregiver Strain Index, Burden Scale for Family Caregiver, Caregiver Burden Inventory, World Health Organization Quality of Life Instrument, Short Form, Caregiver Reaction Assessment, Caregiving Consequences Inventory, Caregiver Burden Scale, Brief Symptom Inventory, Caregiver’s Burden Scale in End of Life, General Health Questionnaire, Thai Burden Interview, Family Appraisal of Caregiving Questionnaire dan Family Caregiver Burden. Kesimpulan dari tinjauan sistematis ini adalah bahwa Zarit Burden Interview (ZBI) merupakan instrumen yag paling banyak digunakan untuk mengukur beban caregiver pada pasien paliatif.Kata kunci: beban caregiver; pasien; perawatan paliatif